Is escherichia coli the only one? Study of causative agents of inflammatory diseases of the urinary system in children of the Zaporizhzhia region - Zakharchenko, N. A.; Захарченко, Наталія Анатоліївна (Запорізький державний медико-фармацевтичний університет, 2023)
Today, antibiotic resistance is a global threat to public health. The main reason is the excessive and inappropriate use of antibiotics. Infections of the urinary system (UTI) are not an exception.
Keywords: тези доповідей